The Meanings of Silence in Indonesian EFL Classrooms - Rizki, Aris Bahari; Andania, Ruqoyyah Amilia; Kusumawati, Eny (Universitas Muhammadiyah Kalimantan Timur, 2025)
This study examines the reasons for students’ silence and the beliefs of students and lecturer about silence in EFL classrooms at Indonesian universities. It explores the perspectives of both students and lecturers on this issue. The participants are three students who are currently assigning as students at the second semester of undergraduate program at one of Indonesian universities and the students’ lecture. The study used semi-structured interviews to collect the data. The study found that students' lack of confidence in speaking English was a major factor contributing to their silence in the EFL classrooms. Some expressed fear of making mistakes or being judged by their peers, which hindered their willingness to participate in class discussions. Additionally, foreign language anxiety was identified as another significant factor, with students feeling overwhelmed and anxious about speaking in a language that is not their first language. Furthermore, the use of silence as a form of politeness was also observed, as students believed that interrupting or speaking out of turn was disrespectful. These factors not only affected students' individual participation but also had an impact on the overall classroom dynamics and communication. The study highlights the importance of addressing these challenges in EFL teaching and suggests strategies such as creating a supportive and non-judgmental classroom environment, incorporating activities that promote confidence-building and oral communication skills, and providing opportunities for students to practice English in a safe and encouraging setting. Overall, the study underscores the significance of understanding the role of silence in communication and its implications for effective EFL teaching in Indonesian universities.